The pathomorfology of changes in rat’s spinal cord in experimental allergic encephalomyelitis after treatment by neuron and glial-enriched fractions of cells of brain - Semenova, V. M.; Lisyany, N. I.; Markova, O. V.; Belskaya, L. N. (Ukrainian Neurosurgical Journal)
The pathomorfologic changes of rat’s spinal cord in experimental allergic encephalomyelitis (EAE) after the neuron and glial-enriched fraction brain cells treatment were investigated. EAE induced by immunization of rats with Freind’s adjuvant and spinal cord tissue gomogenat. Correction was carried on 12-th, 14-th, 16-th day after the induction of the EAE by intraperitoneal injections of newborn brain rat’s neuron and glialenriched fractions. Treament EAE by the brain’s neuronal-enriched fraction was decreased inflammatory infiltration and demyelination spinal brain. The glial cells correction was not changes volume of damage and demyelination.